Dari Aktif ke Pasif: Konstruksi Konseptual Misi Dalam Konteks Indonesia Berdasarkan Yesaya 42:1-9 - Gideon Hasiholan Sitorus (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
This article aims to present and offer a new mission model to renew the traditional mission known as plantation ecclesia or planting the Church amid non-Christian nations. This reality is created from the concept of the mission brought and carried out by the West in colonial territories. , known for its history of colonial expansion, which is understood as the subjugation of adherents of other religions to Christianity. This problem is the basis for the author to carry out a conceptual reconstruction of the mission through consideration of the plural Indonesian context. By setting aside a prescriptive attitude, the mission must be understood as a vocation for everyone to be a model for the world, in other words, to be present and live in the world as it is. It uses descriptive qualitative research methods and narrative analysis of Isaiah 42:1-9. This article closes with the conceptual construction of the mission so that the results show that passive missions can be an alternative. As a result, the mission is not only limited to spreading the faith that is outwardly or centrifugally centered but becomes an inward or centripetal-directed activity, citing A de Kuyper's thoughts. So from an active mission that focuses on finding people or expansive, it transforms into a passive mission that turns inward and rethinks how to get others to come.